Forecasting the prominent, fluctuating and declining stock prices using a numerical approach - et. al., Kavya M, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Stocks and shares play a major role in the economic and financial scenario of a country. When there is a change in the usual economic situation due to any unplanned events or circumstances, the changes in stocks becomes the most prevailing topic. The financial crisis is a major issue that adversely affects most nations. The stock market is a major part of an economy, and when that faces a financial crisis it may lead to a rapid fall in business. Hence, the topic is always an interest of study for the businessmen and academicians across the globe. At present, the stock markets are adversely affected due to the pandemic situation. In this scenario, any type of prediction is helpful. So, we have considered the method of forecasting, which is a powerful tool in estimating future values. This helps investors to overcome significant capital losses. In this paper, we discuss the extrapolation method using mathematical software. It is used to forecast high and low stock prices for upcoming months from the data collected from nseindia.com. Stock market analysis helps the investors to identify the worth of a stock before investing it